Environmentally friendly and degradable electrochemical sensor based on natural bamboo composite conductive polypyrrole and nanosilver, preparation method and application

By cross -compounding pure bamboo chips with polypyel and nano -silver, environmentally -friendly and degradable electrochemical sensor base materials are formed, and the problem that the foundation material is difficult to recycle and reuse in the existing technology is solved. Essence

CN118604075BActive Publication Date: 2025-01-28DALIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411091780.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2025-01-28
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Existing electrochemical sensor substrate materials are difficult to recycle, resulting in electronic waste polluting the environment and being costly.

Method used

The use of pure bamboo chips as the base material, cross -compound composites through the in -situ aggregation and electrical deposition technology to form nano -composite materials, including polypyrum layers and fine willow -shaped nano -silver layers to enhance the electrochemical catalytic performance.

Benefits of technology

The chemical chemical sensor of environmentally friendly and degradable biological electrical electrical electrical electrical electrical electrical electrical electronic electrical electrical electrical electrical electrical electrophoresis is low, and it has high sensitivity and selectivity. It is suitable for detecting formaldehyde and other substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118604075B_ABST
    Figure CN118604075B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of bio-based electronic materials and the field of sensors, and discloses an environmentally friendly and degradable electrochemical sensor based on natural bamboo chips composite conductive polypyrrole and nano-silver, a preparation method and an application. The invention uses pure bamboo chips as a substrate, cross-compounds in-situ polymerization and electrodeposition technology, and compositely embeds conductive polymer polypyrrole by in-situ polymerization. Using FeCl3 as an oxidant and p-toluenesulfonic acid as a dopant, a PPy polypyrrole layer is successfully synthesized on the surface of the bamboo chip, and fine willow-like nano-silver is deposited on the polypyrrole bamboo chip by electrochemical deposition. The nano-silver has a network structure and a large specific surface area, and the nano-silver has a synergistic effect with the polypyrrole interlaced composite, thereby promoting the electrochemical catalytic performance of the sensor. The invention provides an environmentally friendly and degradable electrochemical sensor based on natural bamboo chips composite conductive polypyrrole and nano-silver, a preparation method and an application that are low in cost, simple in preparation, sustainable, green and environmentally friendly, and easy to mass-produce, and the sensor can detect formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bio-based electronic materials and the field of sensors, and in particular to a nano-composite bio-based electrochemical sensor with a pure bamboo substrate and a preparation method thereof. The sensor is environmentally friendly and degradable after use, and has low cost, and is an environmentally friendly and sustainable sensor material. Background Art

[0002] Electrochemical sensors are now widely regarded as a highly sensitive detection tool. Their simple design, convenience, high sensitivity and selectivity in complex matrices, and low waste generation have attracted great attention from the scientific community. Moreover, electrochemical sensing technology is superior to other complex standard instrumental analysis methods such as mass spectrometry, fluorescence measurement, chemiluminescence, capillary electrophoresis, gas chromatography and liquid chromatography, and NMR, which not only have relatively slow analysis times, but also require skilled personnel and high costs.

[0003] The key parts of electrochemical sensors are mainly divided into electrode substrates and multifunctional nano-modified materials. It is reported that the common electrochemical sensor substrates currently include glassy carbon electrodes (GCE), graphite rod substrates (GE), graphite paste substrates (GPE), carbon cloth (CC), screen printing substrates (SPCE), stainless steel substrates (SS), gold electrodes, conductive glass (ITO) substrates, porous electrode (metal foam, graphene foam, etc.) substrates, etc. At the same time, the electrochemical sensors prepared by the above substrates are difficult to recycle and reuse after use, generating a large amount of electronic waste, which is difficult to degrade naturally and imposes a great burden on the environment.

[0004] Bio-based materials mainly refer to materials made from renewable biomass (such as the contents and residues of crops, trees and other plants and animals) as raw materials through biological, chemical and physical means. These materials have the advantages of environmental protection, renewable nature and low carbon emissions. Compared with traditional substrate materials, bamboo bio-based materials have better environmental performance and contribute to the realization of sustainable development. At present, the development of electrochemical sensors with bio-based as sensor substrates still needs further exploration and research. Therefore, the development of electrochemical sensors with excellent performance, low cost and bio-based substrates has certain application prospects and practical significance. Summary of the invention

[0005] In order to make up for the deficiencies of the prior art, the present invention aims to provide a method for preparing a bio-based electrochemical sensor with a pure bamboo substrate which is low in cost, simple to prepare and easy to mass produce.

[0006] The inventive concept of the present invention is: using pure bamboo chips (BC) as the substrate, because the rough porous structure of the surface of the pure bamboo chips and the presence of a large number of oxygen-containing functional groups are conducive to the in-situ polymerization of polypyrrole to promote the doping of conductive polymers, and the rough structure of the surface of polypyrrole and its excellent conductivity are conducive to the electrochemical deposition of silver. The present invention cross-compounds the in-situ polymerization and the electrodeposition technology. Through the in-situ polymerization technology, the nanoparticles can be evenly dispersed into the polymerized monomers or the nanoparticles can be polymerized to form long chains and evenly dispersed on the substrate material to form a stable and non-falling nanocomposite material. Through the electrodeposition technology, the nanocomposite material is cross-compounded to form a stable and dense cross-composite layer material. The fine willow-spike-shaped nanosilver electrochemically deposited by the present invention has a network structure and a large specific surface area, and the cross-composite with polypyrrole produces a synergistic effect, thereby promoting the electrochemical catalytic performance of the sensor.

[0007] Therefore, the bio-based electrochemical sensor based on pure bamboo chips of the present invention is a green and degradable bio-based sensor based on in-situ polymerization of pure bamboo chips and pyrrole to form a polypyrrole layer covering the surface of the bamboo chips and electrochemically depositing nanosilver and polypyrrole to enhance electrochemical catalytic oxidation. The present invention uses the degradable bamboo chips of nature as the base material, and can control the preparation of the bio-based electrochemical sensor based on the pure bamboo chip base composite polypyrrole fine willow spike nanosilver, turning waste into treasure, and embodying an environmentally friendly strategy.

[0008] An environmentally friendly and degradable electrochemical sensor based on natural bamboo composite conductive polypyrrole and fine willow spike-shaped nanosilver, the electrochemical sensor uses bamboo as a base material, and a polypyrrole layer and a silver nanomaterial layer are attached to the surface of the base material. The polypyrrole layer is formed by in-situ polymerization of ferric chloride as an oxidant and p-toluenesulfonic acid as a dopant to form a polymer coated on the surface of the bamboo, and then the fine willow spike-shaped nanosilver is evenly and effectively coated on the surface of the polypyrrole bamboo by electrochemical deposition to form an electrochemical sensor.

[0009] The present invention also claims protection for the preparation method of the electrochemical sensor:

[0010] (1) Preparation of sensor substrate material: The cut bamboo pieces were immersed in acetone solution, ultrasonically cleaned, and dried;

[0011] (2) Preparation of pyrrole solution: prepare a uniform pyrrole solution with a concentration of 0.1 mol / L-1.2 mol / L;

[0012] (3) Preparation of ferric chloride / p-toluenesulfonic acid mixed solution: prepare a uniform mixed solution with a concentration of 0.1 mol / L-1.2 mol / L; the preferred mixing ratio is 1:1;

[0013] (4) Preparation of PPy / BC electrode samples: Place the cleaned and dried bamboo slices into the pyrrole solution and stir evenly in a magnetic stirrer for 5-30 min. Slowly pour the mixed solution prepared in step (3) into the solution and continue to stir slowly. After the polymerization reaction, take out the sample, clean it, and dry it. The preparation of the polypyrrole bamboo slice (PPy / BC) electrode sample is completed.

[0014] (5) Preparation of silver nitrate sodium nitrate solution: prepare silver nitrate sodium nitrate electrolyte solution;

[0015] (6) Preparation of bn-Ag@PPy / BC sensor by electrodeposition of nanosilver: A three-electrode system was selected on the electrochemical workstation, and nanosilver was deposited using constant potential. The PPy / BC electrode sample was used as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V for a deposition time of 1000s to deposit fine willow-tassel-shaped nanosilver on its surface, thus obtaining the nanosilver composite polypyrrole bamboo sheet (bn-Ag@PPy / BC) sensor.

[0016] The sample obtained by in-situ polymerization of conductive polypyrrole layer and electrodeposition of nanosilver is the electrochemical sensor of bamboo substrate composite polypyrrole and nanosilver.

[0017] Furthermore, the bamboo strips in step (1) have specifications ranging from 1 to 10 cm in length, 0.1 to 5 cm in width, and 0.01 to 2 cm in thickness.

[0018] Furthermore, the bamboo pieces are cut into specific specifications, and then the cut bamboo pieces are placed in deionized water for ultrasonic cleaning for 5-20 minutes. After the water on the surface of the bamboo pieces is absorbed dry, the bamboo pieces are placed in an acetone solution for ultrasonic cleaning for 5-20 minutes. Then, the bamboo pieces are taken out from the acetone solution and left until the acetone on the surface evaporates. The bamboo pieces are then placed in anhydrous ethanol for ultrasonic cleaning for 5-20 minutes. Finally, the cleaned bamboo pieces are taken out and placed in a vacuum drying oven at 45°C for drying, and finally taken out and placed in a sealed bag for standby use.

[0019] Furthermore, the step (2) is specifically as follows: selecting a clean beaker and preparing 50 ml of pyrrole solution of different concentrations, wherein ultrasonication is performed for about 5-30 minutes during the preparation process until the pyrrole and water are completely mixed.

[0020] Furthermore, the optimal temperature for the polymerization in step (4) is 25° C. and the time is 120 min.

[0021] Furthermore, step (4) is specifically as follows: select a clean beaker and prepare 50 ml of pyrrole solution of different concentrations, wherein ultrasonication is performed for 5-30 minutes during the preparation process until the pyrrole and water are completely mixed. After the mixture is evenly mixed, the cleaned and dried bamboo chips are added and stirred evenly in a magnetic stirrer for 5-30 minutes. Then the solution prepared in step (3) is slowly poured into the beaker in step (2), and the whole process is still slowly stirred on the magnetic stirrer to maintain a certain polymerization reaction time. After the reaction is completed, the sample is taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45°C, and the preparation of the polypyrrole bamboo chip (PPy / BC) electrode sample is completed.

[0022] Furthermore, the electrolyte solution in step (5) is a mixed solution of 0.01M AgNO3 and 0.1M NaNO3.

[0023] Furthermore, the polymerization reaction of polypyrrole in step (4) and the constant potential deposition of nanosilver in step (6) can be repeated to form multiple layers.

[0024] Furthermore, the in-situ polymerization of polypyrrole in step (4) is performed in a total of 1 to 3 layers.

[0025] Furthermore, the step of electroplating silver in step (6) can be repeated to deposit multiple layers, with a total deposition of 1-3 layers.

[0026] Furthermore, in step (6), a constant potential deposition method is used to apply a potential of -0.4 V and a deposition time of 1000 s to deposit fine willow-tassel-shaped nanosilver on the surface.

[0027] Furthermore, the electrochemical workstation is CHI-660E.

[0028] An environmentally friendly and degradable electrochemical sensor based on natural bamboo composite conductive polypyrrole and nano-silver is prepared according to the above method and can be used to detect liquids, preferably formaldehyde.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The material selection is novel. The present invention uses natural bio-based bamboo chips as the base material, which has significant advantages such as environmentally friendly production, non-toxicity and pollution-free emissions. Bamboo is a natural material with a short growth cycle and low cost. It can grow into tall bamboo trunks and branches in a short time. It is a valuable renewable biological resource and can be degraded into soil nutrients, which is conducive to green environmental protection. The surface of the bamboo chip is rough and contains a large number of oxygen-containing functional groups. The bamboo chip base exhibits a fine hierarchical porous structure, including a large number of micropores and several mesopores. This structure can realize an efficient electron transfer process. The structure is also conducive to composite with functional nanomaterials and is a good base material for sensors. Therefore, preparing sensor materials based on bamboo chips has environmental protection and practical application significance.

[0031] (2) The present invention attaches a polypyrrole layer on the surface of the base material. Polypyrrole (PPy) is a conductive polymer with a large conjugated double bond structure. It has excellent conductivity, high specific surface area and outstanding thermal stability, which is beneficial to enhancing electrochemical catalytic oxidation. Among all conductive polymers, such as polypyrrole (PPy), polyaniline (PAIN) and polythiophene (PTh), polypyrrole not only has good stability and high conductivity, but is also easy to synthesize, and is a good tool for preparing nanocomposite materials.

[0032] (3) The present invention effectively polymerizes pyrrole monomers on the surface of bamboo slices to form a conductive polymer layer through in-situ technology. The preparation process is simple and the cost is low. The polypyrrole layer formed on the surface of bamboo slices is not easy to fall off and has good conductivity. Nanosilver is effectively and evenly coated on the surface of polypyrrole bamboo slices through electrodeposition technology. Polypyrrole and silver nanomaterials can be effectively combined with the biological porous structure of bamboo slices to produce a synergistic effect and form a dense conductive layer. The electrodeposition technology is efficient, environmentally friendly, low-cost, and easy to achieve large-scale production, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a flow chart of the preparation of the electrochemical sensor of the present invention;

[0034] Figure 2 is a surface scanning electron microscope photograph of a pure bamboo chip substrate in an embodiment of the present invention;

[0035] Figure 3 is a scanning electron microscope photograph of an electrochemical sensor prepared in an embodiment of the present invention;

[0036] Figure 4 This is an XRD experimental characterization diagram of the electrochemical sensor prepared in the embodiment of the present invention;

[0037] Figure 5 This is an EDS experimental characterization diagram of the electrochemical sensor prepared in an embodiment of the present invention;

[0038] Figure 6 is the electrochemical response curve of the electrochemical sensor prepared in the embodiment of the present invention to formaldehyde;

[0039] Figure 7 The electrochemical response curve of the electrochemical sensor prepared in the embodiment of the present invention to formaldehyde and the linear relationship curve of the peak current density; (a) the electrochemical response curve of the formaldehyde of different concentrations tested; (b) the linear relationship line with the peak current density;

[0040] Figure 8 The specific selective response and high sensitivity selectivity diagram of the electrochemical sensor prepared in the embodiment of the present invention to formaldehyde (a) The specific selective response diagram to formaldehyde; (b) The high sensitivity selectivity diagram to formaldehyde in different substances;

[0041] Fig. 9 This is a graph showing the degradation mass retention rate of the electrochemical sensor prepared in an embodiment of the present invention in natural soil. DETAILED DESCRIPTION

[0042] In order to more clearly illustrate the purpose, technical solutions and advantages of the present disclosure, the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. It should be understood that the description of the embodiments below is intended to explain and illustrate the overall concept of the present invention, and should not be understood as a limitation of the present invention. For the sake of clarity, the drawings are not necessarily drawn to scale, and some well-known components and structures may be omitted in the drawings. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels. Bamboo chips, silver nanowires and carbon nanotubes were purchased directly on the market.

[0043] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc., are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0044] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected" and "connected" should be understood in a broad sense. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood in specific circumstances.

[0045] The bamboo chips used in the present invention are uncarbonized bamboo chips.

[0046] The bio-based electrochemical sensor comprises a bamboo piece as a base material and a polypyrrole film layer and a silver nanomaterial layer attached to the surface thereof. The polypyrrole layer is formed by in-situ polymerization of ferric chloride as an oxidant and p-toluenesulfonic acid as a dopant to form a polymer coated on the surface of the bamboo piece, and then a layer of nanosilver coated polypyrrole bamboo piece is electrochemically deposited to form an electrochemical sensor. A method for preparing a bio-based electrochemical sensor based on a bamboo piece substrate provided in an embodiment of the present invention comprises the following steps:

[0047] (1) Fabrication of sensor substrate material: Cut bamboo pieces into specific specifications, then place the cut bamboo pieces in deionized water for 5-30 min, then dry the surface water of the bamboo pieces and place them in acetone solution for 5-30 min, then remove the bamboo pieces from the acetone solution and leave them until the acetone on the surface evaporates, then place the bamboo pieces in anhydrous ethanol for ultrasonic cleaning for 5-30 min, finally take out the cleaned bamboo pieces and place them in a vacuum drying oven at 45°C for drying, and finally take them out and place them in a sealed bag for later use;

[0048] (2) Preparation of pyrrole solution: Prepare pyrrole solution with a concentration range of 0.1-1.2 mol / L

[0049] (3) Preparation of ferric chloride p-toluenesulfonic acid solution: prepare 0.1-1.2 mol / L ferric chloride p-toluenesulfonic acid solution;

[0050] (4) Preparation of PPy / BC electrode by in-situ polymerization: Select a clean beaker and prepare 50 ml of pyrrole solution of different concentrations. Ultrasonicate for about 5-30 minutes during the preparation process until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo chips and stir evenly in a magnetic stirrer for 10-30 minutes. Then slowly pour the prepared mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer to maintain a certain polymerization reaction time. After the reaction is completed, the sample needs to be taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45°C to complete the preparation of the polypyrrole bamboo chip (PPy / BC) electrode sample.

[0051] (5) Preparation of silver nitrate and sodium nitrate solution: Prepare a uniform silver nitrate and sodium nitrate electrolyte solution:

[0052] (6) Electrodeposition of silver nanoparticles: A conventional three-electrode system was used on the electrochemical workstation CHI-660E to deposit silver nanoparticles using constant potential. The bamboo slices wrapped with polypyrrole were selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow-like silver nanoparticles on its surface, thus obtaining a silver nanoparticle composite polypyrrole bamboo slice (bn-Ag @ PPy / BC) sensor.

[0053] Example 1 Preparation of sensor samples

[0054] The preparation process is as follows Figure 1 As shown, the specific preparation process is as follows: the bamboo pieces are cut into a specification of 4cm×1cm×0.1cm, and then the cut bamboo pieces are placed in deionized water for ultrasonication for 10 minutes, and then the water on the surface of the bamboo pieces is absorbed and then placed in an acetone solution for ultrasonication for 10 minutes, then the bamboo pieces are taken out from the acetone solution and placed until the acetone on the surface evaporates, and then the bamboo pieces are placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, and finally the cleaned bamboo pieces are taken out and placed in a vacuum drying oven at 45°C for drying, and finally taken out and placed in a sealed bag for standby use.

[0055] Construction of nanosilver composite polypyrrole bamboo strip electrode (bn-Ag@PPy / BC):

[0056] First, select a clean beaker, add 50ml of deionized water and 1750ul of pyrrole, and ultrasonicate the solution for 15 minutes in an ultrasonic instrument until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo slices and stir evenly in a magnetic stirrer for 30 minutes. Then take a clean 100ml beaker, weigh 13.52g of ferric chloride and 9.51g of p-toluenesulfonic acid, add deionized water, and stir until the reagents are completely dissolved. Then slowly pour 50ml of the ferric chloride and p-toluenesulfonic acid mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer, and the polymerization reaction time is 2h. After the in-situ polymerization reaction is completed, take out the sample and thoroughly clean it with deionized water, then dry it in a vacuum drying oven at 45°C, repeat the above steps 3 times, and the PPy / BC sample preparation is completed.

[0057] The traditional three-electrode system was used on the electrochemical workstation CHI-660E, and nanosilver was deposited using constant potential. The bamboo sample wrapped with polypyrrole was selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow-like nanosilver on its surface. It was dried in a vacuum drying oven at 45°C, and the above steps were repeated 3 times to deposit silver, thus obtaining a nanosilver composite polypyrrole bamboo sensor. The microstructure of this sample is shown in the attached figure. Figure 3 shown. Figure 2 The microstructure of the bamboo substrate is Figure 2 It can be seen that pure bamboo pieces have a natural hierarchical pore structure and a rough surface morphology, as well as a large number of oxygen-containing functional groups. This structure is conducive to the in-situ polymerization of PPY and promotes the doping of conductive polymers. The rough structure of the PPY surface and its excellent conductivity are conducive to the electrochemical deposition of silver. Figure 3 As shown, the fine willow-spike-shaped silver nanoparticles electrochemically deposited by the sample sensor have a network structure and a large specific surface area, which produce a synergistic effect with the PPY staggered complex, thereby promoting the electrochemical catalytic performance of the sensor.

[0058] Example 2 Preparation of sensor samples

[0059] The preparation process is as follows Figure 1 As shown, the specific preparation process is as follows: the bamboo pieces are cut into a specification of 4cm×1cm×0.1cm, and then the cut bamboo pieces are placed in deionized water for ultrasonication for 10 minutes, and then the water on the surface of the bamboo pieces is absorbed and then placed in an acetone solution for ultrasonication for 10 minutes, then the bamboo pieces are taken out from the acetone solution and placed until the acetone on the surface evaporates, and then the bamboo pieces are placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes, and finally the cleaned bamboo pieces are taken out and placed in a vacuum drying oven at 45°C for drying, and finally taken out and placed in a sealed bag for standby use.

[0060] Construction of bn-Ag@PPy / BC electrode: First, select a clean beaker and add 50ml deionized water and 350ul pyrrole. Ultrasonicate the solution for 15min in an ultrasonic instrument until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo slices and stir evenly in a magnetic stirrer for 30min. Then take a clean 100ml beaker, weigh 2.7g ferric chloride and 1.9g p-toluenesulfonic acid, add deionized water, and stir until the reagents are completely dissolved. Then slowly pour 50ml of the ferric chloride p-toluenesulfonic acid mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer, and the polymerization reaction time is 2h. After the reaction is completed, the sample needs to be taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45℃. Repeat the above steps 3 times to complete the preparation of PPy / BC samples. Then, the traditional three-electrode system is selected on the electrochemical workstation CHI-660E, and nanosilver is deposited using constant potential. The bamboo PPy / BC sample wrapped with polypyrrole was selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow spike-shaped nanosilver on its surface, and then dried in a vacuum oven at 45°C. The above steps were repeated 3 times to deposit silver, and the bn-Ag@PPy / BC sensor was obtained. The microstructure of this sample is shown in the attached figure. Figure 3 shown. Figure 1 The microstructure of the bamboo substrate is Figure 2 It can be seen that pure bamboo pieces have a natural hierarchical pore structure and a rough surface morphology. Under high magnification, it can be seen that this hierarchical porous structure has numerous micropores and several mesopores. This structure is conducive to providing more active sites for nanocomposites, such as attached Figure 3 As shown in the figure, it can be seen that the fine willow-like silver has been successfully compounded on the surface of the polypyrrole particles, which also proves that the present invention has successfully prepared the bn-Ag@PPy / BC composite electrode. This structure is conducive to the synergistic effect of the two nanomaterials, thereby promoting electrochemical response and sensitivity.

[0061] Example 3 Preparation of sensor samples

[0062] The preparation process is as follows Figure 1 As shown, the specific process is as follows:

[0063] Preparation of bamboo chip samples: The preparation of pure bamboo chip substrate is the same as that in Example 1. After the preparation is completed, it is placed in a sealed bag for standby use.

[0064] Construction of bn-Ag@PPy / BC electrode: First, select a clean beaker and add 50ml deionized water and 700ul pyrrole. Ultrasonicate the solution for 15min in an ultrasonic instrument until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo slices and stir evenly in a magnetic stirrer for 30min. Then take a clean 100ml beaker, weigh 5.4g ferric chloride and 3.8g p-toluenesulfonic acid, add deionized water, and stir until the reagents are completely dissolved. Then slowly pour 50ml of the ferric chloride p-toluenesulfonic acid mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer, and the polymerization reaction time is 2h. After the reaction is completed, the sample needs to be taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45℃. Repeat the above steps 3 times to complete the preparation of PPy / BC samples. Then, the traditional three-electrode system is selected on the electrochemical workstation CHI-660E, and nanosilver is deposited using constant potential. The bamboo chip PPy / BC sample wrapped with polypyrrole was selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow spike-shaped nanosilver on its surface, and then dried in a vacuum drying oven at 45°C. The above steps were repeated 3 times to deposit silver, and the nanosilver composite polypyrrole bamboo chip sensor was obtained. Figure 3 As shown by scanning electron microscopy, fine willow-spike-shaped nanosilver can be seen to be successfully composited onto the bamboo substrate.

[0065] Example 4 Preparation of sensor samples

[0066] The preparation process is as follows Figure 1 As shown, the specific preparation process is as follows:

[0067] Preparation of bamboo chip samples: The preparation of pure bamboo chip substrate is the same as that in Example 1. After the preparation is completed, it is placed in a sealed bag for standby use.

[0068] Construction of bn-Ag@PPy / BC electrode: First, select a clean beaker and add 50ml deionized water and 1050ul pyrrole. Ultrasonicate the solution for 15min in an ultrasonic instrument until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo slices and stir evenly in a magnetic stirrer for 30min. Then take a clean 100ml beaker, weigh 7.2g of ferric chloride and 5.7g of p-toluenesulfonic acid, add deionized water, and stir until the reagents are completely dissolved. Then slowly pour 50ml of the ferric chloride p-toluenesulfonic acid mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer, and the polymerization reaction time is 2h. After the reaction is completed, the sample needs to be taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45℃. Repeat the above steps 3 times to complete the preparation of PPy / BC samples. Then, the traditional three-electrode system is selected on the electrochemical workstation CHI-660E, and nanosilver is deposited using constant potential. The bamboo chip PPy / BC sample wrapped with polypyrrole was selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow spike-shaped nanosilver on its surface, and dried in a vacuum drying oven at 45°C. The above steps were repeated 3 times to deposit silver, and the nanosilver composite polypyrrole bamboo chip sensor was obtained.

[0069] Example 5 Preparation of sensor samples

[0070] The preparation process is as follows Figure 1 As shown, the specific preparation process is as follows:

[0071] Preparation of bamboo chip samples: The preparation of pure bamboo chip substrate is the same as in Example 1. After the preparation is completed, it is placed in a sealed bag for later use.

[0072] Construction of bn-Ag@PPy / BC electrode: First, select a clean beaker and add 50ml deionized water and 1400ul pyrrole. Ultrasonicate the solution for 15min in an ultrasonic instrument until the pyrrole and water are completely mixed. After mixing evenly, add the cleaned and dried bamboo slices and stir evenly in a magnetic stirrer for 30min. Then take a clean 100ml beaker, weigh 9.9g of ferric chloride and 7.6g of p-toluenesulfonic acid, add deionized water, and stir until the reagents are completely dissolved. Then slowly pour 50ml of the ferric chloride p-toluenesulfonic acid mixed solution into the beaker of pyrrole solution. The whole process is still slowly stirred on the magnetic stirrer, and the polymerization reaction time is 2h. After the reaction is completed, the sample needs to be taken out and thoroughly cleaned with deionized water, and then dried in a vacuum drying oven at 45℃. Repeat the above steps 3 times to complete the preparation of PPy / BC samples. Then, the traditional three-electrode system is selected on the electrochemical workstation CHI-660E, and nanosilver is deposited using constant potential. The bamboo chip PPy / BC sample wrapped with polypyrrole was selected as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V and a deposition time of 1000s to deposit fine willow spike-shaped nanosilver on its surface, and dried in a vacuum drying oven at 45°C. The above steps were repeated 3 times to deposit silver, and the nanosilver composite polypyrrole bamboo chip sensor was obtained.

[0073] Example 6 Sensor XRD Characterization Experiment

[0074] The samples were analyzed in detail by X-ray diffractometer (XRD) and compared with the X-ray diffraction patterns of standard materials to gain a deeper understanding of the crystal structure of the samples. Figure 4 As shown in the XRD pattern of PPy / BC, PPy shows a broad amorphous peak at 2θ = 21.99°, which is related to the π-π interaction between PPy molecular chains. Analysis of the XRD pattern of bn-Ag@PPy / BC found that the peaks at 37.8°, 44.2°, 46.01°, 64.33° and 77.44° correspond to Ag (111), Ag (200), Ag (142), Ag (220) and Ag (311) planes, respectively. This also shows that nanosilver was successfully electrodeposited on the PPy / BC electrode, and the bn-Ag@PPy / BC electrochemical sensor was successfully prepared.

[0075] Example 7 Sensor EDS Characterization Experiment

[0076] Energy dispersive spectroscopy (EDS) was used to further analyze the chemical composition and distribution of bn-Ag@PPy / BC. The results are shown in the attached figure. Figure 5 As shown in the figure, carbon (C), nitrogen (N), oxygen (O), sulfur (S) and silver (Ag) elements are all proved to exist and are evenly distributed in the above sample. This also confirms that the sample - nanosilver was successfully deposited on the surface of polypyrrole-coated bamboo by electrodeposition. It also proves that nanosilver and PPy are evenly synthesized on the surface of the bamboo substrate, and the bn-Ag @PPy / BC electrochemical sensor is successfully prepared, as shown in the attached figure. Figure 1 shown.

[0077] Example 8 Electrochemical response experiment of formaldehyde

[0078] The electrochemical response experiment of formaldehyde was carried out on the Chenhua CHI660 electrochemical workstation. In the traditional three-electrode system, bn-Ag @ PPy / BC was selected as the working electrode, saturated calomel was used as the reference electrode, and platinum sheet was used as the counter electrode. The electrochemical analysis of formaldehyde was carried out using differential pulse voltammetry (DPV). The specific operation steps include placing the bn-Ag@PPy / BC sensor in formaldehyde solutions of different concentrations with 0.2 mol / L sodium hydroxide as the solvent, and performing differential pulse voltammetry scanning. The specific setting parameters are initial potential 0.6V, termination potential -1.6V, pulse width 0.05s, pulse period 0.2s, and standing time 2s. Formaldehyde NaOH solutions of different concentrations were prepared as electrolyte solutions using 0.2 mol / L NaOH solution as the solvent, and the response behavior to formaldehyde before and after the addition of HCHO was shown. The results are shown in the attached figure. Figure 6 It can be seen that in the presence of 3mM HCHO, the oxidation peak of formaldehyde appears at around 0 V, and the oxidation current is significantly greater than the oxidation current when no formaldehyde is present. This also shows that the working electrode has a high electrochemical catalytic oxidation activity of formaldehyde. This is because the synergistic effect between PPy and nanosilver has a good catalytic effect on formaldehyde. Then, by differential pulse voltammetry DPV, in a traditional three-electrode system, the sample of Example (1) was selected as the working electrode, saturated calomel was used as the reference electrode, and platinum was used as the counter electrode. The other conditions were the same as the above conditions. Formaldehyde solutions of different concentrations were studied. The test results are shown in the attached figure. Figure 7 As shown, Figure 7 a It can be seen that as the HCHO concentration increases, the peak response current also increases. Figure 7 b It can be seen that within the concentration range of 0.5 mmol / L-4.5 mmol / L, the peak current density and formaldehyde concentration show a good linear relationship, and the linear equation is y = 0.00041x + 0.00195 (R 2 =0.987). The detection limit was calculated to be 0.2488mM (S / N ≥ 3) and the sensitivity was 205μAmM −1 cm −2Therefore, it can be seen that the nanosilver composite polypyrrole proposed in this study can be used as an effective and reliable electrochemical formaldehyde sensor, and the detection limit is expected to be used for the detection of formaldehyde in actual milk samples.

[0079] Example 9 Sensor selectivity experiment for formaldehyde

[0080] The selectivity of the sensor was tested using a traditional three-electrode system on a CHI-660E electrochemical workstation. A saturated calomel electrode was used as the reference electrode, a platinum sheet was used as the counter electrode, and the electrode prepared in Example 1 was used as the working electrode. Differential pulse voltammetry (DPV) was used to perform electrochemical tests on different interfering substances. The test conditions were that 0.2M sodium hydroxide solution contained the same concentrations of propanol, methanol, ethanol, acetone, glacial acetic acid, and n-butanol. The specific setting parameters were an initial potential of 0.6V, a termination potential of -1.6V, a pulse width of 0.05s, a pulse period of 0.2s, and a standing time of 2s. The results are shown in the attached figure. Figure 8 As shown, Figure 8 a It was found that after adding 4.5mM formaldehyde, the DPV curve had an obvious oxidation peak current signal. Figure 8 b The results show that the interfering substances can almost be regarded as background solutions, so the proposed sensor has high selectivity and good anti-interference ability for formaldehyde. This series of formaldehyde electrochemical sensors presents good sensitivity and specificity.

[0081] Example 10 Sensor degradation experiment in nature

[0082] The electrochemical sensor prepared in the embodiment was buried in an open soil. The soil condition required normal growth and survival of plants and normal moisture conditions to carry out the sensor degradation experiment. If the soil moisture was not enough, it was necessary to manually add moisture every 2 days to maintain moist soil conditions to achieve normal degradation of the sensor. Three identical sensor parallel samples were selected and buried in the soil. Three parallel samples were taken out every 3 days to calculate the mass retention rate. After 60 days of degradation, the degradation results are shown in the attached figure. Fig. 9 As shown, the sensor loses about 20% of its mass after being degraded in natural soil, which means that the sensor can be degraded back into nature to achieve an environmentally friendly, green and pollution-free effect.

[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing an environmentally friendly and degradable electrochemical sensor based on natural bamboo composite conductive polypyrrole and nanosilver, characterized in that: The steps include: (1) Preparation of sensor substrate material: ultrasonically clean, dry, seal and set aside the cut bamboo pieces; (2) Preparation of pyrrole solution: prepare a uniform pyrrole solution with a concentration of 0.1 mol / L-1.2 mol / L; (3) Preparation of ferric chloride / p-toluenesulfonic acid mixed solution: prepare a uniform mixed solution with a concentration of 0.1 mol / L-1.2 mol / L; (4) Preparation of PPy / BC electrode samples: Place the cleaned and dried bamboo slices into the pyrrole solution and stir evenly for 5-30 min. Slowly pour the mixed solution prepared in step (3) into the solution and continue to stir slowly. After the polymerization reaction, take out the sample, wash it, and dry it. The preparation of the PPy / BC electrode sample is completed. (5) Preparation of silver nitrate sodium nitrate solution: prepare silver nitrate sodium nitrate electrolyte solution; (6) Preparation of bn-Ag@PPy / BC sensor by electrodeposition of nanosilver: A three-electrode system was selected on the electrochemical workstation, and nanosilver was deposited using constant potential. The PPy / BC electrode sample was used as the working electrode, the mercurous sulfate electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the electrolyte solution was a mixed solution of 0.01M AgNO3 and 0.1M NaNO3. The constant potential deposition method was used to apply a potential of -0.4V for a deposition time of 1000s to deposit fine willow-like nanosilver on its surface, thus obtaining a nanosilver composite polypyrrole bamboo sheet sensor.

2. The preparation method according to claim 1, characterized in that Step (1) The specifications of the bamboo pieces after cutting are as follows: length 1-10 cm, width 0.1-5 cm, thickness 0.01-2 cm.

3. The preparation method according to claim 1, characterized in that The concentration range of the prepared ferric chloride toluenesulfonic acid solution in step (3) is 0.1 mg / mL-1.2 mg / mL, and the mixing ratio is 1:

1.

4. The preparation method according to claim 1, characterized in that: The polymerization reaction of polypyrrole in step (4) and the constant potential deposition of nanosilver in step (6) can be repeated to polymerize or deposit multiple layers.

5. The preparation method according to claim 4, characterized in that: The polymerization of polypyrrole in step (4) is in-situ polymerization, with a total polymerization of 1 to 3 layers.

6. The preparation method according to claim 4, characterized in that: The constant potential deposition of nanosilver in step (6) can be repeated to deposit multiple layers, with a total deposition of 1-3 layers.

7. Application of an environmentally friendly and degradable electrochemical sensor based on natural bamboo composite conductive polypyrrole and nanosilver prepared by the method of claim 1, characterized in that: For specific testing of liquids.

8. The use according to claim 7, characterized in that: Used to detect formaldehyde.

Citation Information

Patent Citations

  • Preparation method of polypyrrole / graphene sheet / nickel oxide nano composite conductive material

    CN103012791A

  • Preparation method of conductive wood aerogel

    CN113119256A